Aktivitas Fisik Mahasiswa Pendidikan Kepelatihan Olahraga selama Pandemi COVID-19 - Wiga Nurlatifa Romadhoni; Nasuka Nasuka; Adiska Rani Ditya Candra; Erwin Nizar Priambodo (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2022)
This study aims to evaluate and at the same time determine the level of physical activity of students in the Sports Coaching Education Study Program using the International Physical Activity Questionnaire (IPAQ). This research is a descriptive study, where this research is used to explain the data collected in the form of data regarding the level of physical activity. The instrument used is a questionnaire from the International Physical Activity Questionnaire (IPAQ). The sample used was 124 students from the 2019 & 2020 classes. This study used a purposive sampling technique in taking research samples. The results show that for the 2019 batch of a total sample of 59, 37.2% of students have a classification of physical activity levels in the high category, 47.5% have moderate/moderate physical activity results and 15.3% have low physical activity results. /low. Meanwhile, for the class of 2020 students with a total sample of 65, 60% of the students were classified as having a high level of physical activity, 18.5% had moderate/moderate physical activity results and 21.5% had low/low levels of physical activity. In conclusion, based on the results of this study, COVID-19 is not an obstacle for students to continue to carry out physical activities during the ongoing COVID-19 pandemic. Keywords: COVID-19, , IPAQ, Physical Activity, Students,